Describing the complexities of developing an eVTOL’s turnaround concept of operations at vertiports - Esteban Navarro, Carlos (Cranfield University, 2025)
Urban Air Mobility (UAM) represents a transformative shift in short-distance transportation, promising fast, sustainable and congestion-free travel using electric Vertical Take-Off and Landing (eVTOL) aircraft. While significant progress has been made in airspace integration and aircraft development, limited attention has been given to ground operations, specifically, the turnaround process at vertiports. This research addresses that gap by exploring the operational, infrastructural and regulatory complexities of eVTOL turnaround, with the aim of supporting the development of a Concept of Operations (ConOps). The study begins with a comprehensive analysis of eVTOL typologies, vertiport classifications and turnaround practices from both fixed-wing and rotary-wing aviation. A thematic literature review reveals a lack of standardised procedures and highlights emerging challenges related to infrastructure, charging, stakeholder roles and scalability. To gain deeper insight, six semi-structured interviews were conducted with stakeholders across consultancy, regulation, manufacturers, infrastructure and ground support services. These were analysed using thematic analysis supported by NVivo software. Findings indicate that eVTOL turnaround is not directly comparable to existing aviation models. Key differentiators include the dominance of electric charging or battery swapping, limited standardisation, the evolving regulatory environment and the need for automation. Stakeholders identified major challenges in assigning responsibilities, ensuring coordination and integrating safety protocols, particularly under constraints of infrastructure size and electricity availability. The study concludes that the development of a flexible, scalable turnaround ConOps is essential for the viability of UAM. While current uncertainties limit the finalisation of standard procedures, early planning and stakeholder engagement can facilitate safer and more efficient operations.
Keywords: UAM; ConOps; challenges; develop; vertical; helicopter; ground; stakeholders; interviews; thematic analysis